Heat-Resistant Ceramic Pigments on the Base of Waste Vanadium Catalyst and Alumina. (24th March 2013) - Sedelnikova, M. B.; Liseenko, N. V.; Pautova, Y. I.; Pogrebenkov, V. M.
Abstract : Ceramic pigments on the base of technogenic silica-containing material—waste vanadium catalyst were obtained in this work. Corundum is identified along with the predominant mullite phase in the composition of pigments. The ions of nickel, chromium, and iron are embedded in the structure if the concentration of the corresponding oxide in the initial mixture does not exceed 10 wt.%. In this case, the oxide is not identified in a free form according to the results of X-ray diffraction analysis. Spinel CoAl2 O4 is formed in cobalt pigments. The developed pigments keep the firing temperature up to 1200°C. The obtained pigments may be recommended for ceramic paints and colored glazes for building materials.